2020
DOI: 10.1088/2053-1591/ab7691
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on structural and optical properties of nanocolumnar ZnTe thin films grown by glancing angle technique

Abstract: In this paper, Zinc Telluride (ZnTe) thin films have been deposited on glass substrate by glancing angle deposition (GLAD) technique at different flux angles. The structural and optical properties of the prepared specimens have been studied with the help of x-ray diffraction (XRD), FESEM, and UV-vis analyses, respectively. According to these tests, remarkable changes in the morphology and the structure of the as-prepared samples have occurred. More significantly, using UV-vis analysis the optical properties in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…[ 1 , 2 , 3 , 4 ], thin layers of zinc telluride (ZnTe) are used in various modern technologies, which are implemented in various micro- and nano-structured devices, such as light emitting diodes, solar cells, photodetectors, etc. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Although it is a popular material, there are few publications and studies regarding its material engineering.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 , 2 , 3 , 4 ], thin layers of zinc telluride (ZnTe) are used in various modern technologies, which are implemented in various micro- and nano-structured devices, such as light emitting diodes, solar cells, photodetectors, etc. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Although it is a popular material, there are few publications and studies regarding its material engineering.…”
Section: Introductionmentioning
confidence: 99%
“…For the deposition of thin layers [ 16 , 17 , 18 , 19 , 20 ], more physical and chemical growth paths are known, such as molecular beam epitaxy (MBE) [ 21 ], chemical bath deposition (CBD), electron-beam evaporation, thermal evaporation, magnetron sputtering [ 12 ], and electrodeposition [ 19 , 20 , 21 , 22 ]. The ZnTe thin layer properties depend directly on the deposition method, deposition conditions, and the growth direction imposed by the substrate when the substrate is crystalline [ 5 , 6 , 7 , 8 , 23 ]. Some studies have established the ideal deposition conditions for various deposition methods, to obtain ZnTe layers with the necessary physical properties, a well-defined morphology, and crystal structure, but there is no systematic reproducible technology available for high performance ZnTe coating fabrications [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, zinc telluride crystals have a potential application in light emitting diodes and photovoltaic cells. It has been reported that the crystalline zinc telluride thin films were able to be synthesized using some crystal growing processes, such as vacuum evaporation [1,2], sputter deposition [3], CVD [4], and electrochemical growth from a non-aqueous solvent [5][6][7][8][9] and from an aqueous solution [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The electrochemical growing technique from an aqueous solvent has an excellent cost-performance in comparison to the other processes and it enables us to coat a conventional wide panel with a practically applicable surface appearance.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Such a possibility of wide range of applications led to several experiments for the synthesis of various ZnTe nanostructures such as quantumdots, nanoplates, thin films, nanowires, nanoribbons, and nanotubes. [24][25][26][27][28][29][30][31][32] For example, Zarei et al [33] synthesized ZnTe thin films by glancing angle technique and observed that they were useful in optoelectronic devices. In a study, Das et al [34] synthesized various ZnTe nanoparticles and reported their size-dependent structural, optical, and vibrational properties.…”
Section: Introductionmentioning
confidence: 99%